2020
DOI: 10.1155/2020/3583806
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Electrochemical Performance of New Flexible Nanocomposite Poly(Vinylidene Fluoride-co-Hexafluoropropylene) Polymer Electrolytes

Abstract: This research paper as an article investigates electrochemical performance of poly(vinylidene fluoride-co-hexafluoropropylene) (PVdF-co-HFP) flexible nanocomposite polymer electrolytes which have been prepared successfully with incorporation of zinc oxide (ZnO) nanofiller. First, nanofillers are incorporated in a polymer matrix to form the flexible nanocomposite PVdF-co-HFP polymer membranes (PI-CMPM), and it is obtained by phase inversion technique. Contact angles of PI-CMPM have achieved a maximum of 136°. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…According to our former work [12], the nanoCMPE with optimized filler content has found that the electrolyte has achieved such as Li + Fig. 2(a-b) shows the surface morphologies of the optimized samples of PVdF-co-HFP based nanoCMPE with 6wt% ZnO filler as dispersoids.…”
Section: Electrochemical Measurementsmentioning
confidence: 87%
See 3 more Smart Citations
“…According to our former work [12], the nanoCMPE with optimized filler content has found that the electrolyte has achieved such as Li + Fig. 2(a-b) shows the surface morphologies of the optimized samples of PVdF-co-HFP based nanoCMPE with 6wt% ZnO filler as dispersoids.…”
Section: Electrochemical Measurementsmentioning
confidence: 87%
“…Addition of filler content increased the porosity >6wt% of ZnO, beyond this filler content, porosity was abruptly decreased due to the aggregation of filler on the polymer matrix. The optimized (6wt%) filler dispersed composite microporous polymer membrane was found to have a high degree of porosity (76%) and more solution uptake (210%) [12] than 8-10wt% filler concentration (Table .1). Pore size and its distribution were the vital factors for solution uptake.…”
Section: Porosity Analysismentioning
confidence: 98%
See 2 more Smart Citations